Changes in the electrochemical response of polycrystalline platinum electrodes promoted by fast repetitive square wave potential signals - Canullo, José Carlos (1984)
There is a great interest in modifying the properties of solid electrodes to achieve their best performance under definite operating conditions. In this sense, at present the preparation, stabilization and reproducibility in the electrochemical response of solid electrode surfaces are subjects of special attention. A recent contribution in this respect that polycrystalline platinum electrodes immersed in acid electrolytes after being subjected to a fast repetitive triangular potential scanning under carefully selected potential perturbation conditions show remarkable changes in the potentiodynamic I/E profiles at v = 0.1 V s -1 corresponding to the H- and O-adatom electroadsorption/ electrodesorption potential region with respect to those of the initial polycrystalline material. These results suggested that the same changes in the electrochemical response of platinum electrodes could be achieved by means of a fast repetitive square wave potential signal covering the potential range of the H- and O-adatom electroadsorption/electrodesorption.